IMPACT OF SODIUM ARSENATE ON SELECTED ENZYMES AND HISTOPATHOLOGICAL STUDIES IN ALBINO MICE - T. DEVARAJU,; K.SUJATHA,; S. MADHAVA RAO,; K. JAYANTHA RAO, (International Journal of Pharma and Bio Sciences, 2010)
Arsenic is a long-known poison of environmental and industrial origin. Prolonged exposure is associated with vascular disease, skin lesions and cancer. The predominant form of arsenic in the nature is the pentavalent arsenate (AsV), which enters the body mainly via contaminated drinking water. Administration of sub lethal dose i.e 4.2 mg/kg/body weight was given to albino mice as single, double and multiple doses. After stipulated period the liver tissue was isolated for enzymes analysis and histopathological studies. The alanine amino transferease (AlAT) activity has shown an increase of 6.03% in single dose, 13.61% in double dose and 27.75% change in multiple dose. Also the activity levels of aspartate amino transferase (AST) has shown an elevation of 9.04% in single, 16.32% in double and 38.08% in multiple dose when compared to control. The glutamate dehydrogenase (GDH) activity has shown an increased level of 9.61% in single, 23.72% in double and 34.62% in multiple doses when compared to control. The liver under sodium arsenate showed necrosis, appearance of vacuoles, nuclear degenerative changes in experimental animals. However, the altered enzymatic and histopathological changes are dose dependent in the present investigation.